Unveiling drimenol: a phytochemical with multifaceted bioactivities - Yang, Zhongming; Chan, Kim Wei; Abu Bakar, Md Zuki; Deng, Xi (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Drimenol, a phytochemical with a distinct odor is found in edible aromatic plants, such as Polygonum minus (known as kesum in Malaysia) and Drimys winteri. Recently, drimenol has received increasing attention owing to its diverse biological activities. This review offers the first extensive overview of drimenol, covering its sources, bioactivities, and derivatives. Notably, drimenol possesses a wide spectrum of biological activities, including antifungal, antibacterial, anti-insect, antiparasitic, cytotoxic, anticancer, and antioxidant effects. Moreover, some mechanisms of its activities, such as its antifungal effects against human mycoses and anticancer activities, have been investigated. However, there are still several crucial issues in the research on drimenol, such as the lack of experimental understanding of its pharmacokinetics, bioavailability, and toxicity. By synthesizing current research findings, this review aims to present a holistic understanding of drimenol, paving the way for future studies and its potential utilization in diverse fields.